Lagrangian photochemical modeling studies of the 1987 Antarctic spring vortex. II - Seasonal trends in ozone - Austin, J.; Jones, R. L.; Mckenna, D. S.; Buckland, A. T.; Anderson, J. G.; Fahey, D. W.; Farmer, C. B.; Heidt, L. E.; Proffitt, M. H.; Vedder, J. F. (1989)
A photochemical model consisting of 40 species and 107 reactions is integrated along 80-day air parcel trajectories calculated in the lower stratosphere for the springtime Antarctic. For the trajectory starting at 58 deg S, which may be regarded as outside the circumpolar vortex, only a small change in O3 occurs in the model. In contrast, for the air parcel starting in the vortex at 74 deg S, the O3 concentration is reduced by 93 percent during the 80 days from the beginning of August to late October. The model results for several species are compared with measurements from the Airborne Antarctic Ozone Experiment and, in general, good agreement is obtained. In the model, the dentrification of the air parcels in polar stratospheric clouds increases the amount of chlorine present in active form. Heterogeneous reactions maintain high active chlorine which destroys O3 via the formation of the ClO dimer. Results of calculations with reduced concentrations of inorganic chlorine show considerably reduced O3 destruction rates and compare favorably with the behavior of total O3 since the late 1970s. The remaining major uncertainties in the photochemical aspects of the Antarctic ozone hole are highlighted.